A new species of Proceratophrys (Anura: Cycloramphidae) from western Brazil - Ávila, Robson W.; Kawashita-Ribeiro, Ricardo A.; Morais, Drausio H. [UNESP] (Magnolia Press, 2011)
A new species of Proceratophrys cristiceps group is described from western Brazil. The new species is characterized by absence of prominent palpebral appendages and postocular swellings, males measuring 44.2 ± 2.1 mm SVL (41.1-47.3 mm) and females 56.4 ± 2.8 mm SVL (52.7-59.8 mm), snout rounded in dorsal ,and obtuse in lateral views, dorsal skin uniformly rugose, with no elevated warts, and tympanum defined as a depression on the skin. The new species was found in Guaporé river drainage, a highly impacted area due to the construction of water dams. Copyright © 2011 Magnolia Press.
Keywords: Amazon; Amphibia; Cerrado; Morphology; Proceratophrys cristiceps group; Proceratophrys strussmannae sp. nov.